Hizbut Tahrir Indonesia's (HTI) Efforts the Idea of Caliphate and Recruit Members after being Banned by the Government - Andri Moewashi Idharoel Haq (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Abstract This paper examines HTIâ€™s efforts to spread the idea of the Caliphate (Khilafah) and recruit new members after the government dissolved them through Perppu Ormas No. 2 of 2017. This paper uses qualitative method through data collection by observation, interviews, and literature review. The result of this research is the following: although the government has banned the HTI, the activities of the movement are still being carried out in resistance to the government ban. In maintaining its activities, HTI uses strategic changes to avoid government control. The strategy focuses on changing the movement from offline activities to online activities and using small groups and informal networks. This strategy is manifested in the Khilafah campaign activities on the internet, such as movies and Islamic studies programs on YouTube. The use of informalnetworks is manifested in the activities of the Campus Daâ€™wah Institution Coordinating Board (BKLDK), which recruits HTI members among students. Another group, the YukNgaji community, was also created to attract the youth through their popular figure, Felix Siauw. This paper argues that even though the government has banned the movement, it has not prevented HTI from furthering its goals of establishing the Caliphate.Â Tulisan ini bertujuan untuk mengkaji upaya HTI menyebarkan ide Khilafah dan merekrut anggota baru setelah mereka dibubarkan oleh pemerintah melalui Perppu Ormas No. 2 tahun 2017. Tulisan ini menggunakan metode kualitatif melalui pengumpulan data secara observasi, wawancara, dan kajian literatur. Hasil penelitian ini ialah meskipun status HTI telah dilarang pemerintah, namun aktivitas gerakan HTI masih tetap dilangsungkan sebagai respons atau perlawanan terhadap kebijakan pemerintah yang membubarkannya. Dalam mempertahankan aktivitasnya, HTI menggunakan perubahan strategi untuk menghindari kontrol pemerintah. Strategi yang digunakan berfokus kepada perubahan area gerakan dari offline ke online dan penggunaan kelompok kecil (jaringan informal) gerakan. Strategi ini berwujud pada aktivitas kampanye Khilafah di internet seperti berbentuk film dan kajian Islam di YouTube. Sementara, strategi penggunaan jaringan informal berbentuk pada penugasan aktivis Badan Koordinasi Lembaga Dakwah Kampus (BKLDK) untuk merekrut anggota HTI di kalangan mahasiswa. Pembuatan kelompok lain yaitu komunitas YukNgaji juga dilakukan untuk menarik minat pemuda melalui figur populer HTI, Felix Siauw. Tulisan ini berargumentasi bahwa meskipun suatu gerakan sosial telah dilarang pemerintah, namun tidak menghalangi aktivitasnya untuk melanjutkan cita-citanya. Contoh pada HTI ini membuktikan bahwa meskipun mereka dilarang, namun aktivitasnya untuk mendirikan Khilafah tetap dilanjutkan.